Pelatihan Desain Untuk Kreatif Meningkatkan Branding Sekolah Pada Pusat Kegiatan Guru Markisa - Minarni; Nurahman; Selviana Yunita (Jurnal Pemberdayaan Masyarakat, 2025)
Graphic design is a medium for conveying information through visual communication language involves aesthetic rules. Social media and digital technology currently have a vital role, especially in the education sector. Based on research results, 95% of respondents agree with the support of information technology in the world of education. One aspect that can be improved is promotion and branding activities of schools to the wider community by utilizing school digitalization. Increasing the skills of teachers is needed to achieve effective school branding and promotion. Interesting, informative and communicative content is an important point in the era of searching for information through social media. On this basis, Darwan Ali University service team holds creative design training activities to improve teacher expertise. This training activity was carried out with teacher participants whose members of the Markisa PAUD (TK and KB) level Cluster Activity Center, Baamang District using Canva application. This research aims to increase the expertise of teachers in creating interesting and communicative content on social media to promote and improve school branding. The training results show that around 86% of PAUD teachers produce content designs for personal and school social media in the form of promotional content and school branding.